A study on the use of measurement software in the preparation of bills of quantities among Malaysian quantity surveying firms - Tan, Chin Keng; Yeoh, Kah Ching (2011)
It is advantageous for a QS to be efficient in producing bills of quantities from measurement. Measurement software applications, as a useful IT tool, can help a QS to speed up the measurement works. In relation to the measurement software application for BQ preparation among Malaysian quantity surveying firms, the objectives of the study are to determine the level of usage, identify the problems and benefits. The data for this study were collected from quantity surveying firms registered in Malaysia. A total of 130 quantity surveying firms were selected as the samples of the survey, representing 41.01% of the total of 317 quantity surveying firms in Malaysia. A total of 34 questionnaires were received for analysis. The study found that less than half of the quantity surveying firms use measurement software in the preparation of BQ. The major problems identified are high software installation cost and required learning and remembering many procedures to use the software. The major benefits identified are high accuracy, easy to edit the BQ, speed up measurement works, and high traceability.